Straightforward incivility scale: adaptation and validation of workplace incivility measurement for portuguese samples - Laneiro, Tito (2023)
The concept of workplace incivility is an underestimated subject in Portugal but a popular one in the international literature. Workplace incivility does not intent to harm others, but it harms workplace norms and put peaceful workplace environment into danger. Thus, the main purpose of this study was to present the adaptation and validation of the Straightforward Incivility Scale (SIS; Leiter & Day, 2013) for Portuguese healthcare professionals’ samples. SIS has 25 items that cover five different sources of Workplace Incivility (WI): supervisors, colleagues, subordinates, customers or the participant her/himself. A Portuguese version of the scale was administered to a total of 737 healthcare professionals from two major public hospital units from the metropolitan area in Lisbon, Portugal (78% women, 83% nurses, 56% with ages from 25 to 34). To assess the factor structure, we submitted these samples to exploratory and confirmatory factor analyses. The results provided psychometric support for the new Portuguese measurement (SIS). Furthermore, it showed good reliability and convergent validity indices with burnout. Considering the mainstream of studies in the healthcare sector, this study adds to the incivility literature as a novel area of research. Furthermore, the study provides a validated version of Straightforward Incivility Scale allowing simultaneous registration of five different workplace incivility sources, while also providing a measurement with good psychometric properties. It is our hope that the workplace incivility can be the focus of future studies measuring its outcomes among healthcare employees as well as to hospital managers and human resources raising awareness within the context of healthcare sector.